TECHNO PARENTING: SINERGI SEKOLAH, LINGKUNGAN SOSIAL DAN ORANGTUA UNTUK MENINGKATKAN MINDFUL DALAM PENGASUHAN ANAK - Asep Munajat; Dadan Rahmat; Ibnu Hurri (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2023)
A common understanding between parents, schools and how to shape the social environment to educate children can determine educational success. Children's problems at school cannot be separated from parenting patterns at home and how the child's social environment is formed. Children's success at school is also supported by the parenting style that children receive in their family environment, including their social environment. Therefore, education carried out at school must be in synergy with education carried out in the family. Synergy can be built when parents are able to communicate well with the school, but with the various activities that parents have, regular meetings are difficult to hold so that a common understanding of parenting is difficult to develop, besides that with advances in technology parents are freeing their children to use digital technology, in this case Android . Parents allow their children to use Android without restrictions and considering the impacts that will arise, inappropriate use of technology can result in addiction to devices, pornography, health hazards and radiation. Techno parenting is a digital parenting program design through an Android application about how to educate children in the digital era in utilizing technology. Apart from that, Techno parenting is a strategy that can be used to build effective communication between schools and parents through digital technology to increase awareness/mindfulness in educate. Mindful parenting is a concept in parenting that emphasizes the process of parenting with full awareness (awareness). Therefore, the objectives of this research are 1) collaborating on technological advances in parenting education, 2) synergy between parents and schools in building the same perception regarding children's education, 3) developing a technology parenting model in increasing parental awareness (playfulness) in parenting, and 4) knowing The effectiveness of the techno parenting model in increasing mindfulness in parenting. The research method used is development research with stages of Analysis, Design, Development, Implementation and Evaluation where each stage is used to produce Techno Parenting Model products. The evaluation results show that parenting technology is effectively used in the ABA 7 Kindergarten school, Sukabumi Regency.